The Sursuk Family and Land Dealings in Ottoman Palestine: A Historical Perspective (1890-1920) - Bektas, Erhan (SETA FOUNDATION, 2025)
In the late 19th century, the Jewish migration to Palestine had a wide range of political, economic, and social impacts that have continued to the present day. The belief of the Jews that the land of Palestine was promised to them constituted one of the principles on which the migration movement was based and one of the main factors that motivated migration. The Zionist Community's backing was a major factor in the background of Jewish immigration to Palestine of the Ottoman Empire. One of the activities of this Zionist organization in Palestine was to purchase the land on behalf of the Jews through the Sursuk family, one of the rich landowners of the region. By selling the properties they held in Palestine to Jewish settlers, the Sursuks contributed to the permanent settlement of Jews. This article will examine the Sursuk family's involvement in the sale of Palestine to Jews, considering Ottoman Archive documents. These documents, which cover the years 1890-1920, provide details on how Palestinian territories were sold to Jewish settlers via the Sursuks. This study also aims to understand the overall picture of land sales by touching upon the multidimensional regional/international cooperation established by the Sursuk family.
Keywords: Palestine; Sursuk Family; Property Sales; Zionist Jewish Society; Government & Law